Parents’ and Adolescents’ Willingness to be Vaccinated Against Serogroup B Meningococcal Disease during a Mass Vaccination in Saguenay–Lac-St-Jean (Quebec) - Eve Dubé; Dominique Gagnon; Denis Hamel; Sylvie Belley; Hélène Gagné; Nicole Boulianne; Monique Landry; Julie A Bettinger (Canadian Journal of Infectious Diseases and Medical Microbiology)
A mass vaccination campaign with the 4CMenB vaccine (Bexsero®; Novartis Pharmaceutical Canada Inc) was launched in a serogroup B endemic area in Quebec. A telephone survey was conducted to assess parental and adolescent opinions about the acceptability of the vaccine. Intent to receive the vaccine or vaccine receipt was reported by the majority of parents (93%) and adolescents (75%). Meningitis was perceived as being a dangerous disease by the majority of parents and adolescents. The majority of respondents also considered the 4CMenB vaccine to be safe and effective. The main reason for positive vaccination intention or behaviour was self-protection, while a negative attitude toward vaccination in general was the main reason mentioned by parents who did not intend to have their child vaccinated. Adolescents mainly reported lack of interest, time or information, and low perceived susceptibility and disease severity as the main reasons for not intending to be vaccinated or not being vaccinated.